Efficacy and Safety of Second‐Line Immune Checkpoint Inhibitor Rechallenge in Advanced or Metastatic Esophageal Squamous Cell Carcinoma: A Retrospective Study - Wensi Zhao; Nan Zhao; Dedong Cao (Thoracic Cancer, 2025)
ABSTRACT Background Immune checkpoint inhibitor (ICI) has reshaped the treatment landscape of esophageal squamous cell carcinoma (ESCC). But most patients end up with disease progression and/or therapeutic intolerance. The subsequent ICI rechallenge raises some discussions. Methods A retrospective study was conducted to assess the efficacy and safety of reintroduction of ICI in patients with advanced or metastatic ESCC after first‐line ICI failure. Outcomes included median overall survival (OS), progression‐free survival (PFS), objective response rate (ORR), disease control rate (DCR) and safety. Subgroup analysis and prognostic analysis were also performed. Results A total of 1320 patients were screened and 138 were enrolled: 109 received second‐line ICI‐based therapies, and 29 received non‐ICI therapies. As of data cutoff on November 30, 2024, patients with ICI rechallenge, compared with non‐ICI rechallenge, achieved an improved second‐line OS (10.4 vs. 5.8 months; HR = 0.53, 95% CI: 0.33–0.84; p = 0.006) and showed a favorable PFS trend (5.0 vs. 3.0 months; HR = 0.75, 95% CI: 0.48–1.17; p = 0.202). The 6‐month PFS rate was 42.9% versus 22.3%, and the 12‐month OS rate was 41.5% versus 23.2%, respectively. The ORR was 30.3% versus13.8% and the DCR was 79.8% versus 58.6%, respectively. ICI combined with chemoradiotherapy was the most popular option for subsequent ICI rechallenge, with an OS of 11.2 months. Treatment‐related adverse events of grade ≥ 3 occurred in 47 (43.1%) and 11 (37.9%) patients in the two groups. Conclusion Second‐line ICI rechallenge provided OS benefits in advanced or metastatic ESCC, with manageable safety. Further prospective study is warranted.